Cultural Capital Management with Collaborative Mechanism for Sustainable Elevate Economic Value of Kui Ethnic Group who Herdered Elephant in Surin Province - Sukthong, Chalong; Suktong, Autcharaporn; Potisarn, Wijittra; Intawee, Peerawas; Phayakkanant, Siwaporn; Nualnang, Warit; Samaksamarn, Sombat; Somban, Pahdol (Research Community and Social Development Journal, 2024)
Background and Objective: Managing a community’s cultural capital requires cooperation across all sectors and studying the local context. The objective of this research is to study the cultural capital management model and create a mechanism for cooperation to raise sustainable economic value. of the way of the elephant herders of the Kui ethnic group Surin Province. Methology: Mixed methods research Set a specific target group of 30 people using surveys, interviews, observation notes and questionnaires with content validity of the questions between 0.67-1.00. Data collection was done by going to the field to organize activities with the group. Targets and stakeholders in the area Data were analyzed using descriptive analysis along with descriptive statistics to find frequencies and percentages. Results: The model for managing cultural capital for the elephant herders of the Kui ethnic group has 5 steps: 1) survey and create a digital map of cultural capital 2) develop digital media 3) develop a cultural route for elephant households 4) design creative products and Raise the standard of community products. 5) Promote awareness of value and create cultural value. For the mechanism of cooperation to raise sustainable economic value of the Kui Elephant Shepherd ethnic group, there are 6 mechanisms: 1) creation and collection of resources 2) sharing of resources 3) building relationships 4) research and development of local culture 5 ) skill development and exchange of knowledge and 6) participatory communication and public relations. Discussion: Cultural capital management model and cooperation mechanism to raise economic value sustainably It can be considered a sustainable development process for the Kui ethnic elephant herder community. Surin Province Can create cultural value Raise the economy in the long term and create complete sustainability for the community. Covers the expectations and needs of people in the community. Suggestion: Important operations It requires the creation of cooperation among all stakeholders and the community. To promote and provide budgetary support Training in project management knowledge and skills and developing appropriate, sustainable and high-impact cultural activity plans.